PPKN SUBJECTS CHANGED TO PANCASILA EDUCATION, HOW IS IT IMPLEMENTED? - Muthia Rahman Nayla; Paiman Paiman; Evie Farida Sulaeman (Jurnal Multidisipliner Bharasa, 2022)
Pancasila subjects that will be applied in the 2022/2023 school year have gone through a long journey in education, especially the learning process. Historically, the world of education has known PMP (Pancasila Moral Education) and PPKn (Pancasila and Citizenship Education). Since the year of reform, the subject that discusses Pancasila has undergone many changes, both in terms of material and the basic foundation of the curriculum in education itself. This is a result of one of them is the amendment of the 1945 Constitution. This paper aims to determine the implementation of Pancasila subjects that will be applied as a substitute for PPKn subjects. Research is a type of normative or literature research. Data collection through literature review is related to the focus of research in the form of literature review, theory, and documents. Meanwhile, data analysis is carried out descriptively by triangulation. Hasilresearch shows that the Ministry of Education and Culture early 2022 issued guidelines for implementing the curriculum to recover learning after the Covid-19 pandemic. It contains Pancasila subjects that replace PPKn subjects. Its implementation is carried out by considering 2 (two) aspects, namely: intracurricular allocation per year; and the allocation ofPancasila student profile projects. Keywords: Subjects, PPKn, Pancasila.